Enhancing customer service through employee engagement in the service sector: a comparative study of a hotel and a tour operator in Victoria Falls, Zimbabwe - Bhebhe, M.; Nyanhete, T. (Midlands State University, 2015)
The aim of this paper is to ascertain how customer service could be enhanced through employee engagement. Lack of documented evidence of the contribution of employee engagement to customer service improvements in the service sector in Zimbabwe motivated the researchers to carry out this study. Customer service is at the heart of business growth and survival for organisations in the service sector. It therefore became imperative for this study to establish the contribution of employee engagement initiatives towards enhancing customer service. Organisations in Zimbabwe are focusing on re-capitalisation and re-industrialisation with the belief that organisational success may be enhanced, relegating people focus to a secondary status. However, a study on engagement within the service industry in Zimbabwe was therefore essential to ascertain the value of placing employee engagement at the centre of business success in enhancing customer service. The sample size for the study was 66 and the research adopted a mixed methodology approach, were a detailed description of employee engagement was given while also making some statistical illustrations. The approach took a comparative case study design using two service organisations a hotel and a tour operator. Research instruments used to collect data included questionnaires and interviews. The findings of the research showed that 58% employees in the tour operating company were engaged and strategies such as employee share ownership schemes, training and development opportunities and competitive reward packages were in place in that company than in the hotel were engagement level stood at 39%. The conclusion drawn is that customer service could be enhanced through strategically employing and implementing human resource practices that foster employee engagement. A number of recommendations were put forward by the researchers that could improve engagement levels of shopfloor employees in both organisations in order to attain high standards of customer service.